Principal Leadership Typology in Improving the Quality of Education at Muhammadiyah 1 Ponorogo Middle School - Afrizal Afrizal; Afiful Ikhwan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to answer two research questions: identifying the leadership typology of the principal of Muhammadiyah 1 Junior High School, Ponorogo, and analyzing their contribution to improving the quality of education at the madrasah. The focus of this research is based on the principal's strategic role as a director, manager, and innovator, who determines educational programs and the achievement of service quality. This study used a qualitative approach with descriptive-analytical methods. Data were collected through observation, in-depth interviews, and documentation analysis that illustrated actual leadership practices. Process analysis was conducted inductively and deductively to identify leadership patterns and summarize their links to improving educational quality. The research results indicate that school principals apply democratic, humanistic, and collective leadership typologies. This typology is evident in decision-making patterns involving teachers and the school committee, attention to the welfare and professional needs of educators, and cross-stakeholder collaboration in implementing school programs. Principals also combine their roles as educators, managers, supervisors, and innovators to strengthen the digitalization of learning, improve teacher competency, and develop student achievement programs. This approach creates a conducive, collaborative, and quality-oriented learning environment. Based on these findings, the research recommends strengthening accountability systems to ensure a more structured collective process, as well as regular evaluation of innovative and digital programs to ensure their relevance to student needs and educational development.